The automated calculation of difficult frame designs - Akhazhanov, S.B.; Karataуev, G.K. (Bulletin of the Karaganda University. Mathematics Series, 2015)
In this work the automated calculation of difficult frame designs is considered. For calculation of frame designs the method of final elements is used. The general matrix of rigidity of a final element is found. The main dependence of a final element is received. An example of calculation of rigid frame designs is reviewed. Results are given in a tabular form and curve the internal of efforts are constructed. Numerical results are compared to analytical decisions.